Implications of Online Learning: Trends of Science Misconceptions about Forces in Elementary School - Munastiwi, E.; Saputro, B.; Fatonah, S.; Suhendro, E. (Jurnal Pendidikan IPA Indonesia, 2022)
This study aims to understand the tendency of science misconceptions about "forces" and to distinguish the influence of school origin on students' misconceptions. The research method is a quantitative experimental survey. A total of 83 fourth-grade elementary school students from public school 1 (School A), private school 2 (School B), and private school 3 (School C) were involved in this study. Data is collected through online surveys. Teachers and researchers formulated question instruments in the form of quizzes. Before being distributed, the synchronization and verification stages of the material are carried out. Then the quiz is distributed to students via WhatsApp during an online class. After 15 minutes, students return the answers to the class teacher in photos via WhatsApp to be evaluated and graded. The results show that the average level of students' misconceptions was relatively low. However, the level of individual misconceptions tended to be high, proving that the development of learning practices needs to pay attention to conceptual understanding. Students misconceptions should not occur, especially in science learning. This study concludes that there are differences in the level of misconceptions between clusters in science learning. Students in each cluster experienced similar obstacles. The researchers suggest an effort to adjust the learning model on the instructional, interaction, supervision, and independent learning models.